Pengawasan Parkir Ilegal Di Kota Tasikmalaya Melalui Colaboratif Governance - Sapari, Cepi Triana; Samkamaria, Samkamaria (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
This research aims to describe the supervision of illegal parking in the city of Tasikmalaya through the implementation of collaboration with community components or interest groups. The research shows that supervision consists of three stages: Standard Setting (SOP), Result Measurement, and Deviation Evaluation. identification of deviations by illegal parking practitioners and certain officials, and the collaborative process that has not been effective due to the lack of follow-up from the collaboration process. Based on the criteria of collaborative governance that have not been met, particularly in the aspects of distributive accountability and access to resources. The criteria indicate a lack of involvement from other stakeholders in the collaborative forum and a shortage of financial resources.